DAPSA and ultrasound show different perspectives of psoriatic arthritis disease activity: results from a 12-month longitudinal observational study in patients starting treatment with biological disease-modifying antirheumatic drugs. Issue 2 (5th November 2018) - Pukšić, Silva; Bolton-King, Pernille; Sexton, Joseph; Michelsen, Brigitte; Kvien, Tore K; Berner Hammer, Hilde
Abstract : Objectives: Disease Activity index for PSoriatic Arthritis (DAPSA) (sum score 68/66 tender/swollen joint counts (68TJC/66SJC), patient's global assessment, pain and C-reactive protein (CRP)) is recommended for clinical assessment of disease activity in patients with psoriatic arthritis (PsA). Ultrasound (US) (grey scale (GS) and power Doppler (PD)) detects inflammation in joints and extra-articular structures. The present objectives were to explore the longitudinal relationships between DAPSA, clinical assessment as well as patient-reported outcome measures (PROMs) with US in patients with PsA initiating biological DMARDs and the associations between DAPSA and US remission. Methods: 47 patients with PsA were examined at baseline and after 3, 6, 9 and 12 months. Assessments included 68TJC/66SJC, examiner's global assessment (EGA), PROMs, CRP, erythrocyte sedimentation rate (ESR) and US GS and PD (48 joints, 10 flexor tendons, 14 entheses, 4 bursae). Clinical composite scores and PD sum scores (0=remission) were calculated. Longitudinal associations were explored by generalised estimating equations with linear and logistic regression. Results: DAPSA was not longitudinally associated to PD. 66SJC, ESR, 28-joint Disease Activity Score, EGA and CRP were longitudinally associated with PD (p<0.001–0.03), whereas the pain-related components of DAPSA (68TJC and pain) as well as PROMs were not associated. At 6–12 months, remission was achieved in 29%–33 % of the patients for DAPSA and 59%–70 % for PD. The association between DAPSA and PD remission was not significant (p=0.33). Conclusions: DAPSA was not associated with US inflammatory findings which indicates that DAPSA and US may assess different aspects of PsA activity.